2011
DOI: 10.5539/jsd.v4n2p16
|View full text |Cite
|
Sign up to set email alerts
|

A Delphi Study to Identify Corporate Social Responsibility Indicators: The Case of Greek Telecommunication Sector

Abstract: The Telecommunication sector deals with numerous social and operational challenges such as technological development, increased demand for telecommunication services, health concerns and environment protection. The aim of this paper is to identify both general and sector-specific indicators in order to measure the Corporate Social Responsibility (CSR) performance. The Telecommunication sector has analyzed and identified the main stakeholders that affect and are affected by business operations. Six main stakeho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 85 publications
0
8
0
7
Order By: Relevance
“…Type IV measured the impacts of CSR on stakeholders and financial performance (Inoue, Kent, & Lee, 2011;Walker, Heere, Parent & Drane, 2010;Walker & Kent, 2009;Walters & Tacon, 2010). Finally, type V deliberated measurement of corporate social performance (Duygu, 2009;Giannarakis, Litinas, & Theotokas, 2011;Tsai, Cheng, & Chang, 2012;Wood, 2010). Babiak and Wolfe (2006) analyzed the CSR activities hold by the Super Bowl, found that by doing "good things", sport organizations can not only ease the negative criticism caused by unethical behavior, but enhance their image and reputation.…”
Section: Introductionmentioning
confidence: 99%
“…Type IV measured the impacts of CSR on stakeholders and financial performance (Inoue, Kent, & Lee, 2011;Walker, Heere, Parent & Drane, 2010;Walker & Kent, 2009;Walters & Tacon, 2010). Finally, type V deliberated measurement of corporate social performance (Duygu, 2009;Giannarakis, Litinas, & Theotokas, 2011;Tsai, Cheng, & Chang, 2012;Wood, 2010). Babiak and Wolfe (2006) analyzed the CSR activities hold by the Super Bowl, found that by doing "good things", sport organizations can not only ease the negative criticism caused by unethical behavior, but enhance their image and reputation.…”
Section: Introductionmentioning
confidence: 99%
“…For the telecommunication sector, Mudzamir and Norfaiezah (2007) recommend fi ve stakeholders: the environment, welfare or charity, community involvement, products or services, and natural disasters. Giannarakis et al (2011) defi ne the CSR in six domains or stakeholders by analyzing the CSR annual reports of the Greek telecommunication companies. Additionally, the Delphi method was developed so that executives could both recommend CSR indicators and rank the importance of and corporate governance (or CSR).…”
Section: Csr Domains and Indicatorsmentioning
confidence: 99%
“…Th e fi rst recommends equal weights, whereas the second recommends diff erent weights concerning the relative importance of indicators to society. Giannarakis et al (2010) analyze the results of Giannarakis et al (2011), indicating that there is no agreement regarding the importance of indicators in each stakeholder domain, except customer and human resources. Th e weights used for each domain and sub-domain are presented in Figure 1.…”
Section: Csr Domains and Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taneja et al (2011) categorized CSR research into five major types. Type one discussed the meaning, definition, and model of CSR (Carroll, 1979(Carroll, , 1999(Carroll, , 2010Dahlsrud, 2008;Van Marrewijk, 2003); type two identified factors determining CSR (Lange & Washburn, 2012;Wu, 2014); type three analyzed actions of CSR (Oberseder, Schlegelmilch, & Murphy, 2013;Babiak & Trendafilova, 2011;Bravo, Matute, & Pina, 2012); type four identified the effects of CSR on stakeholders and financial performance (Chih et al, 2014;Lombart & Louis, 2014;Lu, Chau, Wang, & Pan, 2014;Oberseder et al, 2013); type five explored the measurement tools of corporate social performance (Giannarakis, Litinas, & Theotokas, 2011;Turker, 2009;Wood, 2010;Wagner, Bicen, & Hall, 2008). Extensive research has been conducted on CSR; however, little research has addressed the concerns of CSR (i.e., CSiR), which is a major gap in consumer behavior research.…”
Section: Csr and Csirmentioning
confidence: 99%